(untitled) (Revista Inclusiones, 2020)
This article addresses the development of information technology that makes major contribution in efficiency enhancement of most business processes and, because of this, is the most important benchmark of competitive advantage of financial companies in the market. Introduction. Development of non-financial services in the banking market brings Russia to a new level of the range of customer services offered. Objective. Financial institutions that provide cloud services undergo major changes under the influence of information technology. Cloud services ensure savings thanks to equipment standardization, virtualization, new features of software application sharing and payment of the new form of resource utilization by customers, which will be the main driver of the global IT market for the next ten years. Materials and methods. Methods of research and data base analysis, synthesis of data collected into theoretical conclusions and practical guidelines have been used. Methodologically and theoretically, the study is based on scientific works of home and foreign scientists in the theory and practice of economic and financial provision.